Theory of Islamic consumer behaviour : an empirical study of consumer behaviour of Islamic mortgage in Malaysia - Amin, Hanudin; Abdul Rahman, Abdul Rahim; Abdul Razak, Dzuljastri (Emerald Publishing Group, 2013)
The purpose of this study is to propose a theory of Islamic consumer behavior to explain the factors that influence the Islamic mortgage industry. Although previous works have shown that conventional marketing theories were, to a certain extent, able to predict factors influencing halal marketing and Islamic mortgage, these theories fail to capture or accommodate the Islamic perspectives of consumer behavior. Conventional marketing theories have also been preference found to be inadequate to explain the Islamic mortgage among consumers.